APLIKASI CHATTING AKAKOM CAREER CENTER (MEMBUAT CHATTING SEPERTI WHATSAPP) - Indra Yatini; F. Wiwiek Nurwiyati; Rini Rini (Universitas Janabadra, 2017)
Communication is one of the most important things humans need in life. In this case chat is used to communicate directly to fellow internet users who are online. With the chat application we can send messages to others who are online, then the intended person will reply to the message, and so on. The current growing technology can be used for various things, especially in solving problems to convey information. One such technology is to use Node JS and Socket.IO technology to implement chat application required for AKAKOM Career Center to convey information about career services as well as to be used for media discussion of AKAKOM Career Center with alumni. The results of this research are implemented into a web application that can be used to convey information by sending and receiving messages within the provided chat page. Keyword: Node JS, Chatting, Socket.IO, MongoDB.